A proposal to solve the problem of moral luck in the context of the principle of control - STRZYŻYŃSKI, PRZEMYSŁAW (Filozofia Chrześcijańska, 2021)
The article presents a proposal of solution of the problem of moral luck in the context of the principle of control. This principle states that the condition for assigning responsibility, moral guilt / merit is to have control over the action by the perpetrator. According to his supporters, a moral hit causes the moral evaluation of a subject's action that was disturbed by chance or a factor beyond the subject's control. The article tries to show that there is no complete lack of control in the actions that are affected by chance. Hence, one cannot put forward such distant consequences of the impact of luck on morality as the negation of the rationality of assigning moral responsibility and blame / merit in general. Instead, the article proposes to assign moral responsibility separately from guilt / merit, depending on the intention of the acting subject.